Ketahanan Panas Cemaran Escherichia coli, Staphylococcus aureus, Bacillus cereus dan Bakteri Pembentuk Spora yang Diisolasi dari Proses Pembuatan Tahu di Sudagaran Yogyakarta - Reny Mailia; Bara Yudhistira; Yudi Pranoto; Saiful Rochdyanto; Endang Sutriswati Rahayu (agriTECH, 2015)
Characteristics of tofu with higher a (0.89 to 0.90) and protein levels of 8% or more, made tofu to be a suitable medium for bacterial growth. This leads to out to be very easy to damage due to bacterial contamination. Contamination of bacteria is commonly found in the tofu because of contamination in the process making of tofu. Source of contamination can come out from the raw material, during the process of making tofu and hygienic sanitation level during processing. Generally, this study aimed to determine the level of contamination of Escherichia coli, Staphylococcus aureus, Bacillus cereus and spore-forming bacteria in the process of making tofu and study the properties of heat resistance of eachisolate. Phases of of the study started with the isolation and identification and then quantitative analysis of Escherichiawcoli, Staphylococcus aureus, Bacillus cereus and spore-forming bacteria in the tofu process from raw materials to end product, tofu, comprised from water and soybean, slurry, soymilk cooking, curd, whey and tofu. Isolates originating from the cooking process and the coagulation process was for testing the heat resistance (D value and Z value). D and Z values were calculated using linear regression. Escherichia coli found in the water, soybeans, soybean slurry, curd and tofu, the number 10 =4,83 min and the value of Z = 22.73°C. Staphylococcus aureus found in soybeans and curd, showed the number of 101-102 CFU/g. Escherichia coli GMP isolate had D60°C CFU/g. The Staphylococcus aureus GMP4 isolate, had D60°C 1=2.72 min and the value of Z = 18.87°C. The Staphylococcus aureus GMP 6 isolate, had D=2.54min and the value of Z = 18.18°C. Bacillus cereus found in the water, soybean, soybean slurry, soymilk cooking, curdand tofu, showed the number 102-103CFU/g. Bacillus cereus vegetative cells SK 2 had D=5.43 min and the value of Z = 22.72°C. Bacillus cereus vegetative cells SK 4 had D60°C 60°C =5.95 min and the value of Z = 22.22°C. Spore-forming bacteria found in water, soybean, soybean slurry from the grinding process, the process cooking of soymilk, the process of clotting, whey and tofu, showed the number of 102CFU/g.ABSTRAKKarakteristik tahu dengan a0,89-0,90 dan kadar protein 8% atau lebih, menjadikan tahu sebagai media yang cocok bagi pertumbuhan bakteri. Hal ini menyebabkan tahu menjadi sangat mudah rusak karena cemaran bakteri. Penelitian ini bertujuan untuk mengetahui tingkat cemaran Escherichia coli, Staphylococcus aureus, Bacillus cereus dan Bakteri pembentuk spora pada proses pembuatan tahu dan mempelajari sifat ketahanan panas dari masing-masing cemaran. Tahapan penelitian dimulai dari pengamatan proses pembuatan tahu, isolasi dan identifikasi dan analisa kuantitatif cemaran Escherichia coli, Staphylococcus aureus, Bacillus cereus dan bakteri pembentuk spora pada proses pembuatan tahu. Isolat yang berasal dari proses pemasakan dan proses penggumpalan digunakan untuk pengujian ketahanan panas dengan melihat nilai D dan Z menggunakan regresi linier. Escherichia coli ditemukan pada air, kedelai, bubur kedelai, gumpalan tahu dan tahu, dengan jumlah 10w1-10CFU/g. Isolat Escherichia coli dari proses penggumpalan (GMP), nilaiD60°C 2=4,83 menit dan nilai Z=22,73°C. Staphylococcus aureus ditemukan pada kedelai, gumpalan tahu dan tahu, dengan jumlah 10=2,72 menit dan nilai Z =18,87°C. Untuk isolat Staphylococcus aureus GMP 6, nilai D1CFU/g.  Isolat Staphylococcus aureus GMP 4, memiliki nilai D60°C60°C =2,54 menit dan nilai Z =18,18°C. Bacillus cereus ditemukan pada air,kedelai, bubur kedelai, sari kedelai masak, gumpalan tahu dan tahu, dengan jumlah 102-10CFU/g. Sel vegetatif Bacilluscereus yang berasal dari sari kedelai (SK) 2, memiliki nilai D60°C3=5,43 menit dan nilai Z =22,72°C. Untuk sel vegetatif  Bacillus cereus SK 4, memiliki nilai D60°C=5,95 menit dan nilai Z =22,22°C. Bakteri pembentuk spora ditemukan pada air, kedelai, bubur kedelai pada proses penggilingan, sari kedelai masak, gumpalan tahu, kecutan dan tahu, dengan jumlah 10CFU/g.